Thyroid Hormone and Blood Metabolites Concentrations of Broiler Chickens Subjected to Feeding Time Restriction - A Azis; H Abbas; Y Heryandi; E Kusnadi (Faculty of Animal Science, Bogor Agricultural University, 2012)
The present study was conducted to determine the effect of feeding time restriction on thyroid hormone and blood metabolites concentration of broiler chickens during feed restriction and realimentation period. Four hundred of 7 days-old unsexed broiler chicken of Lohmann commercial strain were arranged in a completely randomized design with 5 treatments and analyzed based on ANOVA. The treatments were: chicks fed ad libitum as a control treatment (R-0); chicks had free access to feed during two periods of 2 h (08:00-10:00 and 16:00-18:00) from 7-14 d of age (R-1) and 7-21 d of age (R-2); chicks had free access to feed during two periods of 4 h (08:00-12:00 and 16:00-20:00) from 7-14 d of age (R-3) and 7-21 d of age (R-4). The treatments consisted of 4 replicates with 20 chicks each. During feeding time restriction from 7 to 21 d of age, thyroid hormone and albumin plasma concentration of R-2 and R-4 were lower (P3 and T4) and blood metabolite (albumin) decreased during feeding time restriction for 4 and 8 h per d from 7 to 21 d of age and it returns to normal during realimentation period.